Collagen fibre characterisation in arterial tissue under load using SALS. (November 2017) - Gaul, R.T.; Nolan, D.R.; Lally, C.
Abstract: The collagen fibre architecture of arterial tissue is known to play a key role in its resultant mechanical behaviour, while maladaptive remodelling of this architecture may be linked to disease. Many of the techniques currently used to analyse collagen fibre architecture require time consuming tissue preparation procedures and are destructive in nature. The aim of this study is to fully explore Small Angle Light Scattering (SALS) as a means to non-destructively assess collagen fibre architecture in arterial tissue and subsequently gain insights into load induced reorientation. The optimised configuration of the SALS system for arterial tissue was determined using quantitative comparisons to histological analyses of porcine carotid artery as its basis. Once established, layer specific fibre orientation and the influence of tissue loading was determined for thin sections of carotid artery using SALS. This process was subsequently repeated for intact carotid artery layers. A single family of circumferentially orientated collagen fibres were found in the intima (− 0.1 ± 1.4° (5.5°)) and media (− 1.7 ± 1.9° (4.7°)) while two perpendicular families of fibres were identified in the adventitia (− 6.4 ± 0.7° (37.7°)) and (118.3 ± 2.7 (39.9°)). An increase in fibre alignment in response to a 20% circumferential strain was also identified using SALS, characterised by an increase in scattered light eccentricity. Results: determined using SALS agreed with those found using traditional destructive techniques, however SALS has the important benefits of allowing vessel layers to remain intact, and has a fast processing time. SALS unique ability to identify load induced reorganisation in intact arterial layers offers an efficient means to gain crucial insights into arterial disease and its development over time. Highlights: A Small Angle Light Scattering (SALS) system was optimised for arterial tissue. SALS was capable of establishing fibre distributions in intact vessel layers. SALS identified single and multiple collagen fibre families across the vessel wall. Graphical abstract: fx1